2009
DOI: 10.1055/s-0029-1240689
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavonoids from the Roots ofCampylotropis hirtella

Abstract: From the dried roots of Campylotropis hirtella (Franch.) Schindl., five novel isoflavonoids, 3( S)-7,2',4'-trihydroxy-5,5'-dimethoxy-6-(3-methylbut-2-enyl)-isoflavan ( 1), 3( S)-2',4'-dihydroxy-5,5'-dimethoxy-(6'',6''-dimethylpyrano)-(2'',3'':7,6)-isoflavan ( 2), 3( R)-5,4'-dihydroxy-2'-methoxy-3'-(3-methylbut-2-enyl)-(6'',6''-dimethylpyrano)-(7,6 : 2'',3'')-isoflavanone ( 3), 3( R)-5,4'-dihydroxy-2'-methoxy-(6'',6''-dimethylpyrano)-(7,6: 2'',3'')-isoflavanone ( 4), and 3( R)-5,4'-dihydroxy-7,2'-dimethoxy-6-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…0 -geranyl-5,7,2 0 ,5 0 -tetrahy-droxyisoflavone (5), myrsininone A (6), isosophoranone (7), and myrsininone B (8) through analysis of spectroscopic data and by comparison with previous studies [22][23][24] . The exact chemical structures were fully determined from spectroscopic data including 2D-NMR (Figure 1 Human neutrophil esterase inhibitory activity HNE is controlled by its endogenous inhibitors, like a1-antitrysin, but the affinity of these endogenous inhibitors for HNE is strongly decreased by oxidative stress and by proteases released upon inflammation.…”
Section: Characterization Of Human Neutrophil Elastase Inhibitory Commentioning
confidence: 93%
“…0 -geranyl-5,7,2 0 ,5 0 -tetrahy-droxyisoflavone (5), myrsininone A (6), isosophoranone (7), and myrsininone B (8) through analysis of spectroscopic data and by comparison with previous studies [22][23][24] . The exact chemical structures were fully determined from spectroscopic data including 2D-NMR (Figure 1 Human neutrophil esterase inhibitory activity HNE is controlled by its endogenous inhibitors, like a1-antitrysin, but the affinity of these endogenous inhibitors for HNE is strongly decreased by oxidative stress and by proteases released upon inflammation.…”
Section: Characterization Of Human Neutrophil Elastase Inhibitory Commentioning
confidence: 93%
“…Previous chemical studies revealed that the plant C. hirtella contains tannins (Qin et al 1991), steroids, triterpenes (Lu et al 1997), flavonoids , coumarins , lignans , C-glycosylfavones and aromatic glycosides (Wen et al 2007). More than 50 new flavonoids were isolated from C. hirtella in our laboratory (Shou, Fu, et al 2009;Shou et al 2009a;Shou et al 2009b;Zhang et al 2010;Tan et al 2011;Li et al 2014), and some of these flavonoids were found to possess very interesting biological activities. For example, Hirtellanine A ( Figure 1) showed significant inhibitory activity against B lymphocyte proliferation.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…MTT (5 mg/mL) reagent was added 4 h before the end of culture, the supernatants discarded, and the cells lysed with DMSO. The OD 570 values of the samples were obtained, and the percentage of cell death was calculated [12].…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…Its dried roots are used as a traditional Chinese medicine for the treatment of irregular menstruation, dysmenorrhea, metrorrhagia, and metrostaxis as well as gastric ulcers [2]. Various chemical entities including tannins, steroids, triterpenes, flavonoids, coumarins, lignans, C-glycosylfavones, and aromatic glycosides have been isolated from this plant [3][4][5][6][7][8][9][10][11][12][13]. Our previous study revealed that a coumaronochromone from this plant possesses very potent immunosuppressive activity [11] and, as a continuation of our work identifying promising immunosuppressants from this Chinese medical material, eight new flavonoids were isolated from the dried roots of C. hirtella (three pterocarpenes, 1, 2, 3; two flavanones, 4, 5; and three isoflavones, 6,7,8).…”
mentioning
confidence: 99%